Pengaruh Kompleksitas Tugas Terhadap Kualitas Audit Dengan Disfungsional Auditor Sebagai Variabel Moderasi - Fitria Magdalena Suprapto; Wawan Cahyo Nugroho (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
The auditor is the most important part of the assessor component of an organization’s financial statements. People who need financial information as a basis for making decisions expect the independence of public accountants in assessing financial statements so that in order to maintain reputation, auditors are always required to be careful in maintaining audit quality. This study aims to examine the effect of task complexity on audit quality with auditor dysfunctionality as a moderating variable. The research sample used auditors who work in KAP located in Surabaya with the sampling technique using purposive sampling method. The source of research is the primary which comes from the collection of survey on respondents to obtain individual opinion. There are 66 questionnaires that meet the criteria to be sampled. Hypothesis testing uses linear regression and moderated regression analysis. The results showed that task complexity had an effect on audit quality. Dysfunctional auditors are not able to moderate the complexity of the task on audit quality